2021
DOI: 10.1101/2021.10.23.465567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Impacts Carbon Metabolism and Depends on Glutamine for Replication in Syrian Hamster Astrocytes

Abstract: Coronaviruses belong to a well-known family of enveloped RNA viruses and are the causative agent of the common cold. Although the seasonal coronaviruses do not pose a threat to human life, three members of this family, i.e., SARS-CoV, MERS-CoV and recently, SARS-CoV2, may cause severe acute respiratory syndrome and lead to death. Unfortunately, COVID-19 has already caused more than 4.4 million deaths worldwide. Although much is better understood about the immunopathogenesis of the lung disease, important infor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
4
0
2
Order By: Relevance
“…In line with the potential neurotropic properties of SARS-CoV-2, recent evidence has demonstrated the presence of viral proteins in brain regions of COVID-19 patients as well as in the brains of K18-ACE2 transgenic mice infected with SARS-CoV-2 2123 and syrian hamsters 24 . The presence of SARS-CoV-2 in the human brain has been associated with significant astrogliosis, microgliosis and immune cell accumulation 21 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In line with the potential neurotropic properties of SARS-CoV-2, recent evidence has demonstrated the presence of viral proteins in brain regions of COVID-19 patients as well as in the brains of K18-ACE2 transgenic mice infected with SARS-CoV-2 2123 and syrian hamsters 24 . The presence of SARS-CoV-2 in the human brain has been associated with significant astrogliosis, microgliosis and immune cell accumulation 21 .…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, astrocytes are responsible for maintaining glutamate levels in the brain 69,70 . Recently, de Oliveira et al showed that glutamine levels were reduced in mixed glial cells infected with SARS-CoV-2 and that the inhibition of glutaminolysis decreased viral replication and pro-inflammatory response 24 . Hence, given the importance of the coupling between astrocytes and neurons, alterations in astrocytic glucose and glutamine metabolism are expected to compromise neuronal function, affecting neuronal metabolism and synaptic function and plasticity 71 .…”
Section: Discussionmentioning
confidence: 99%
“…The main complications derived from SARS-CoV-2 infection are related to systemic oxygen shortage due to lung tissue damage as a result of exacerbated immune activation and virus replication, which lead to metabolic changes that prepare target organs and tissues to reduced oxygen supply [ 39 ]. Leaving aside the metabolic reshaping provoked by the virus on infected cells [ 40 , 41 ], it has been proposed that critical metabolic changes occur in endothelial and immune cells in the early stages of lung damage [ 40 ]. Moreover, if oxygen levels do not recover, the decrement in oxygen supply may lead to further damage to critical organs such as brain, kidneys, and liver [ 42 , 43 ], as observed in critical COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was verified that ACE2 was predominantly localized in the pericytes from the mouse microvessels (Wenzel et al, 2021). Further studies showed that SARS-CoV-2 is able to directly infect neural stem cell-derived astrocytes (Crunfli et al, 2020) and hamster astrocytes (de Oliveira et al, 2021), and that SARS-CoV-2 spike protein was present in different cells from brain of patients, the majority of these cells being astrocytes (Crunfli et al, 2020).…”
Section: Introductionmentioning
confidence: 93%